The needs of graduates required by the employment industries: analysis of English language speaking course outlines at Pakistani universities - Ayub, Sadia; Khaleel, Badriah (Journal of Language and Pragmatics Studies, 2024)
Since a syllabus is an essential teaching tool, it should contain relevant content and a well-organized curriculum based on practical skills needed at the workplace. Proficiency in spoken English can unlock a wealth of international career prospects. Despite the Higher Education Commission's efforts to improve the educational landscape, elevated levels of joblessness are hampering advancement. The primary goal of this qualitative study was to examine the functional English-speaking course outline at the BS level in private and public Pakistani universities. English language course outlines (communication and presentation skills) were collected from various private and public universities that were conveniently available to the researcher. Data from employed graduates was collected through purposive sampling techniques. Additionally, data was collected from 10 recently employed graduates through a questionnaire to explore the job needs of BS English language students in Pakistan. As the research was qualitative, data was collected using a purposive sampling technique. For reliability, the research questionnaire was validated by three subject matter experts. The syllabi need to be presented more coherently and meet most of the ideal syllabus's requirements. The English language speaking course outlines were found to focus on grammar and give little attention to speaking skills required for the workplace. The study recommends creating an efficient speaking skills-based English language course outline at the BS level for both HEC and university authorities based on the survey data collected from recently employed graduates.